2013
DOI: 10.3402/edui.v4i3.22629
|View full text |Cite
|
Sign up to set email alerts
|

Variations in grading practice – subjects matter

Abstract: This article aims to explore the relevance and importance of school subjects in teachers' grading practices, as teachers themselves see it. The study is based on material from 41 semi-structured interviews, with teachers of five subjects, at four lower and two upper secondary schools in Norway. The findings suggest that the school subject does matter when teachers assign final grades to their students. The study also indicates that different subjects involve different challenges or obstacles in fulfilling gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 27 publications
0
12
0
5
Order By: Relevance
“…Finally, assessment in learning environments, which includes new genres and multimodal texts, is a delicate matter. Research has shown that it is often difficult to alter established assessment practices (Prøitz, 2013). Even though many scholars have pointed out the need to develop effective tools for assessing new types of texts in schools, there is also a need for more knowledge about how assessments are enacted in naturally occurring classroom interactions.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Finally, assessment in learning environments, which includes new genres and multimodal texts, is a delicate matter. Research has shown that it is often difficult to alter established assessment practices (Prøitz, 2013). Even though many scholars have pointed out the need to develop effective tools for assessing new types of texts in schools, there is also a need for more knowledge about how assessments are enacted in naturally occurring classroom interactions.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…An early 20th-century text on grading systems, for example, laments that the "variability in the marks given for the same subject and to the same pupils by different instructors" causes "real injustice" for students (Finklestein, 1913, p. 6). Current research on grading practices continues to explore variability, not only across institutions and educational systems, but also between teachers in the same system (Biberman-Shalev, Sabbagh, Resh, & Kramarski, 2011;Proitz, 2013;Randall & Engelhard, 2010;Resh, 2009). Grade inflation, the phenomenon of grade point averages rising without commensurate increases in achievement, is another area of ongoing research (Organisation for Economic Co-operation and Development, 2012;Pattison, Grodsky, & Muller, 2013).…”
mentioning
confidence: 99%
“…Many researchers have contrasted language and mathematics teachers' grading practices (e.g., Pasquini, 2019;Thorsen & Cliffordson, 2012), underlining that each discipline has its own grading style: mainly performance oriented for the former and more effort centered for the latter (Biberman-Shalev et al, 2011). Regarding mathematics, teachers tend to consider grading to be easier than in other subjects (Prøitz, 2013), and they seem to pay particular attention to their students' progress and achievement (Braxmeyer et al, 2005). However, holistic grading practices remains more challenging for mathematics teachers compared to language teachers, in part because of the characteristics of disciplinary subjects (Meier et al, 2006;Pasquini, 2019).…”
Section: Research On Gradingmentioning
confidence: 99%